ANALISIS PENJUALAN PAKAIAN PADA PERUSAHAAN PERSEORANGAN PRIMA JAYA LESTARI MENGGUNAKAN METODE AUTOREGRESSIVE INTEGRATED MOVING AVERAGE (ARIMA) - Ferawaty, Ferawaty; Jeslyn, Jeslyn (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2020)
Since 1993, PP Prima Jaya Lestari is a business engaged in convection and garment, especially batik and men's shirts. Currently, PP Prima Jaya Lestari has used a computerized system to record and manage business transaction data. However, the system is unable to provide information on the influence of millennial clothing trends on to increasing convection sales at the company. To solve the problem in PP Prima Jaya Lestari, the method that being used is Auto Regressive Integrated Moving Average (ARIMA) method. In the working procedure, the stationarity of the data in the mean can be done by identifying the data plot and the ACF data form. If ACF shows a slowdown pattern means the data is not stationary in the mean, so it requires differencing so that the data becomes stationary in the mean. Conversely, if the ACF shows a rapidly descending pattern, the data is statistical in the mean Based on the results of the tests conducted in this study obtained information that by using the MAE method to calculate the difference in clothing sales between the real value and the predicted result value, information was obtained that the type of plain shirts and men's tile motif shirts have a greater MAE value when compared to the type of men's batik shirts and men's lyrical motif shirts, which means that the error rate of predictions against plain shirt types and men's tile motif shirts is much greater. This is because the type of men's batik shirts and men's lyrical shirts have a sales turnover that tends to be more stable. Meanwhile, the type of plain shirts and men's tile motif shirts have a more volatile sales turnover.